Antibiotic Use Pattern in Orthopaedics and Traumatology Ward: A 6 Month Survey in A Tertiary Hospital - Ethelie, Stanislaus Gerald; Tjahjadi, Adi Imam; Primadhi, Andri (International Journal of Integrated Health Sciences, 2019)
Objective: To determine and describe the antibiotic use pattern in the orthopedics and traumatology ward of Dr. Hasan Sadikin General Hospital Bandung as a tertiary hospital in West Java, Indonesia.Methods: A retrospective cross-sectional study using the total sampling method was performed on the medical records of orthopedics and traumatology patients treated using antibiotics during the period of January 1, 2016 and June 31, 2016.Results: From the 261 subjects who met the inclusion criteria, it was discovered that the most common antibiotics used were in the following order: cefazolin (54.41%), ceftriaxone (21.84%), and cefotaxime (10.35%). Most antibiotics (75.86%) were given as prophylaxis. Antibiotics were most often administered for 2-3 days (42.53%), intravenously (97.7%), andÂ  with a dose of 2x1 gram (92.16%).Conclusion: The most frequently used antibiotics in the orthoaedics and traumatology ward of Dr. Hasan Sadikin General Hospital (RSHS) was cefazolin, which was mostly used as a pre-surgical antibiotic. The use of third-generation cephalosporin antibiotics as pre-surgical antibiotics is still observed during this study.Â